The Effect of Work Life Balance and Perceived Organizational Support on Work Engagement in Female Employees of PTPN I Regional 4 Surabaya - Della Widya Pramudita; Sulastri Irbayuni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Women deciding to pursue a career has caused a shift in the main role of women. The increase in the number of female workers is due to the equal opportunity between women and men in obtaining higher education. However, in reality, there are many challenges that must be faced by married women when they decide to start their careers. In dealing with this phenomenon, work-life balance and organizational support are needed to increase the work engagement of female employees in the company. The purpose of this study was to determine the effect of work life balance and perceived organizational support on work engagement. The method used is a quantitative method with a population of 40 married female employees of PTPN I Regional 4 Surabaya and sampling techniques using saturated samples, namely samples taken to represent the entire population. Data were obtained through a questionnaire which was compiled based on indicators of each research variable and then analyzed using SmartPLS software. The results of the study showed the influence of work life balance and perceived organizational support on work engagement.